(untitled) (Meridiano 47 - Journal of Global Studies, 2017)
FORST, Rainer; “Toleration in Conflict: Past and Present”; Cambridge University Press, United States of America, New York, 2013; 662 pp. ISBN: 978-0-521-88577-5 Hardback